Peculiarities of spelling the Chinese syllables ju, qu, xu, yu - Гуль, О. Г. (Studia Philologica, 2019)
Considering the significance and actuality of the Chinese syllables: their phonetic sounding and peculiarities of pronunciation, the proposed article will focus on the syllables which are regarded to be a difficult phonetic aspect. The main goal of this article is to become a brief guide of the correct and incorrect spelling for the Chinese syllables “ju”, “qu”, “xu” and “yu”, and to bring clearance into understanding of the necessity to spell the Chinese character correctly, in accordance with the basic phonetic laws. The article provides the rules of correct spelling, frequent spelling mistakes, syllable peculiarities and difficulties in understanding the main point of the statement, while being pronounces incorrectly. The article will reveal that the background of the issue is hidden in the formation of pinyin, and the consecutive process of its reformation and simplification. The information and research, provided in the article will be supported by the fundamental pinyin Chart, shown in two parallels: the original Chinese writing and spelling of the syllables, on the one hand and the spelling, offered by the Archimandrite Palladyi for the transcription and transliteration of the Chinese syllables into Cyrillic script, on the other.